Constructing a Core Collection of the Medicinal Plant Angelica biserrata Using Genetic and Metabolic Data - Liu, Man; Hu, Xin; Wang, Xu; Zhang, Jingjing; Peng, Xubing; Hu, Zhigang; Liu, Yifei (Frontiers in Plant Science, 2020)
Angelica biserrata is an important medicinal plant in Chinese traditional medicine. Its roots, which are known as Duhuo in Chinese, are broadly applied to treat inflammation, arthritis, and headache. With increasing market demand, the wild resources of A. biserrata have been overexploited, and conservation and breeding cultivars of this species are needed. Germplasm resources are the material basis for protecting genetic diversity and cultivating good breeds. A core collection must be constructed to preserve, evaluate, and utilize germplasm resources. Here, we used simple sequence repeat markers which derived from transcriptome datato construct an A. biserratacore collection based on samples collected from Changyang-related regions. We found abundant genetic diversity within populations of A. biserrata and the clustering analysis resulted into two sample groups. A further metabolic analysis of these samples revealed the main coumarin contents, such as osthole and columbianadin. According to the genetic and metabolic data, we adopted the least distance stepwise sampling strategy to construct seven preliminary core collections, of which the 20CC collection, which possessed 42 A. biserrata individuals accounting for 90.91% of the genetic diversity of the original germplasm, represented the best A. biserrata core collection. This study will contribute to the conservation and management of A. biserrata wild germplasm resources and provide a material basis for future selection and breeding of this medicinal plant. This collection will be a representative reference for constructing core collections in other medicinal plants.